The Role of ICT in Science Education - Medh, Punam (Indian Journal of Educational Technology, 2020)
ICT is helping to bring in a change in the way schools teach and assess students. The use of ICT is especially making inroads in the possibilities of how science is taught; going from rote-learning to developing higher order thinking skills like building scientific temper and critical thinking. To enable this journey, ICT makes available two types of interventions; content-based applications with rich multi media effects that explain concepts and software applications which help in data collection, documenting – thus helping children build knowledge actively rather than watch a readymade multimedia passively. Experts of education prefer the latter because in these applications lie the potential to reshape pedagogy, not just support it. The use of ICT in science education by itself cannot bring about change unless, we as educators consciously plan on how and where to use it within the teaching - learning processes in the classroom. The use of ICT in science can also holds the promise to bring in more constructivist learning experiences.